Improving students' motivation and self-confidence in speaking using mingling games - Fransiskus Karsudianto (English, 2020)
This study aims to improve the students' intrinsic motivation and self-confidence in speaking by using mingling games. This study was carried out in one of the junior high schools in Bengkayang county. It employed a classroom action research method. The study was done in two cycles involving one English teacher as a collaborator and 24 junior high school students as the subject of the research. The data collection techniques were gained through interviews, observation, document, and questionnaire. The instruments used are interview guidelines, field notes, observation checklist, lesson plans, and questionnaire guidelines. Since the research is classroom action research, the research procedure includes four stages: planning, acting, observing and reflecting. Before starting the procedure, a preliminary study was conducted to find the problem. The finding reveals that the implementation of mingling games is successful to improve the students’ motivation and self-confidence in speaking practice. The information gained from this study can be worthwhile considerations for teachers to enhance their knowledge dealing with a teaching strategy in improving the students' intrinsic motivation and self-confidence in speaking.